Information Technology Adoption by Internal Auditors in Public Sector: Antesedents and Consequences - Koesanto, Stefani Made Ayu Artharini; Husnatarina, Fitria; Rahmaddian, Rahmaddian; Madya, Faizal (Jurnal Organisasi dan Manajemen, 2021)
The understanding of Information Technology (IT) adopted by internal government auditors is related to developments in the IT sector in the public sector, such as e-government applications. The purpose of this study is to provide an argument for the motivation for IT adoption when the internal auditors and to identify the factors that influence IT adoption and the influence of IT adoption on the performance of internal auditors in the public sector. This research used quantitative methods and data analysis using Structural Equation Modeling (SEM) with 79 auditors from the Inspectorate within the scope of Central Kalimantan Province. Findings. The results showed that only the perceived benefits variable had a positive and significant effect on IT adoption, while the compatibility variables, top management support, organizational readiness, the external force had a positive but insignificant effect on IT adoption as an antecedent part, while IT adoption had an effect, positive and significant impact on government performance as a consequence of IT adoption. This study provides a practical understanding for government auditors that in carrying out their duties, especially in the new normal order conditions, that the adoption of IT is important to do to produce a good performance.